CHARACTER OF RELATIONSHIP BETWEEN SOMATIC COEFFICIENTS AND PHYSIOLOGICAL PARAMETERS THE 15-17 YEAR OLD ICE-HOCKEY PLAYERS - Szmatlan-Gabrys, Urszula Barbara; Gabrys, Tomasz Tytus; Stanula, Arkadiusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The somatic structure in the significant degree determines the possibilities of applying definite tactical solutions, he can limit or stimulate unreeling the competitor individual technique. Somatic conditions can be the limiter of the motor preparation and coordination. The aim of investigations was qualification of dependence between coefficients of the somatic parameters and coefficients of aerobic and anaerobic efficiency. In investigations participated hockey players of National Team Poland in the age from 15 to 17 years. Essential dependences stepped out between the coefficients of aerobic and anaerobic efficiency, and the coefficients of the somatic conditions counted from the value of mass and the length of the body. The number of appointed dependences is higher in hockey players team U18 in the comparison with hockey players team U15.